Dental mineralization and salivary activity are reduced in offspring of spontaneously hypertensive rats (SHR) - Elias, Gracieli Prado [UNESP]; Santos, Otoniel Antonio Macedo dos [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Silva, Cristina Antoniali [UNESP] (Journal Of Applied Oral Science : Revista Fob, 2006)
Several pathologies have been diagnosed in children of hypertensive mothers; however, some studies that evaluated the alterations in their oral health are not conclusive. This study analyzed the salivary gland activity and dental mineralization of offsprings of spontaneously hypertensive rats (SHR). Thirty-day-old SHR males and Wistar rats were studied. The salivary flow was evaluated by injection of pilocarpine, the protein concentration and salivary amylase activity, by the Lowry method and kinetic method at 405 nm, respectively. Enamel and dentin mineralization of the mandibular incisors was quantified with aid of the microhardness meter. The results were analyzed by the ANOVA or Student's t test (p<0.05). It was noticed that the salivary flow rate (0.026 mL/min/100 g±0.002) and salivary protein concentration (2.26mg/mL±0.14) of SHR offspring were reduced compared to Wistar normotensive offspring (0.036 mL/min/100 g±0.003 and 2.91 mg/mL±0.27, respectively), yet there was no alteration in amylase activity (SHR: 242.4 U/mL±36.9; Wistar: 163.8 U/mL±14.1). Microhardness was lower both in enamel (255.8 KHN±2.6) and dentin (59.9 KHN±0.8) for the SHR teeth compared to the Wistar teeth (enamel: 328.7 KHN±3.3 and dentin: 67.1 KHN±1.0). These results suggest that the SHR offspring are more susceptible to development of pathologies impairing oral health, once they presented lesser flow and salivary protein concentration and lower dental mineralization.

Diversas patologias têm sido diagnosticadas em filhos de mães hipertensas, entretanto alguns estudos que avaliaram as possíveis alterações na saúde oral não são conclusivos. Neste trabalho foram analisadas a atividade das glândulas salivares e a mineralização dental de filhotes de ratas espontaneamente hipertensas (SHR). Ratos machos, com 30 dias de vida, SHR e Wistar, foram estudados. O fluxo salivar foi avaliado pela injeção de pilocarpina e a concentração de proteínas e atividade da amilase na saliva, pelo método de Lowry e método cinético a 405 nm, respectivamente. A mineralização do esmalte e dentina de incisivos inferiores foi quantificada através da medida da microdureza. Os resultados foram analisados pelo teste ANOVA ou t de Student's não pareado (p<0,05). Verificou-se que o fluxo salivar (0,026 mL/min/100 g ± 0,002) e a concentração de proteínas na saliva (2,26 mg/mL ± 0,14) de filhotes SHR estavam reduzidos em comparação com filhotes normotensos Wistar (0,036 mL/min/100 g ± 0,003 e 2,91 mg/mL ± 0,27, respectivamente), porém sem nenhuma alteração da atividade da amilase (SHR: 242,4 U/mL ± 36,9, Wistar: 163,8 U/mL ± 14,1). A microdureza mostrou-se menor tanto no esmalte (255,8 KHN ± 2,6) quanto na dentina (59,9 KHN ± 0,8) dos dentes de SHR em comparação com os de Wistar (esmalte: 328,7 KHN ± 3,3 e dentina: 67,1 KHN ± 1,0 ). Estes resultados sugerem que filhotes SHR seriam mais susceptíveis ao desenvolvimento de patologias que prejudicam a saúde oral, uma vez que apresentaram fluxo e concentração proteica salivares reduzidos e menor mineralização dental.
A mineralização dental e a atividade salivar estão reduzidas em filhotes de ratas espontaneamente hipertensas (SHR)
Keywords: Spontaneously hypertensive rat (shr); Tooth mineralization; Hypertension; Uniterms; Hipertensão; Rato espontaneamente hipertenso (SHR); Saliva; Mineralização de dente